PENGARUH OTONOMI AUDIT DAN AMBIGUITAS PERAN TERHADAP KINERJA AUDITOR - Galih Chandra Kirana (Jurnal Liabilitas, 2022)
The results showed that the Auditor's Work Results as measured by the level of Role Ambiguity did not have a positive and significant effect on Auditor Performance and Audit Autonomy as measured by the results of the work completed by the auditors had a positive and significant effect on Examiner Performance.